Evaluation of suicide patterns, causes and triggering factors in children and adolescents - Büşra Baydemir Kılınç; Mustafa Talip Şener (BMC Pediatrics)
Abstract This study aims to enhance understanding of child and adolescent suicide by raising awareness of the issue and analyzing the socio-demographic characteristics, suicide methods, and triggering factors associated with these cases. A total of 47 pediatric suicide cases were analyzed based on forensic autopsy reports conducted at the Erzurum Forensic Medicine Group Presidency between 1 January 2018 and 31 December 2024. The mean age of the subjects was 15.32 years, with the majority belonging to the 15–17 age group. Suicides predominantly occurred in rural areas and at home. The most common method was firearm injury (51%), followed by hanging (42.6%). Violent methods were used in all cases. A proportion of the cases (10.6%) had diagnosed psychiatric disorders, and a similar proportion (10.6%) originated from broken families. Triggering factors included family conflicts, relationship problems, and pregnancy. Suicides were generally more common in the summer months. Easy access to firearms in rural areas and family conflicts were identified as significant risk factors for suicide. To prevent suicide among children and adolescents, it is important to raise social awareness, strengthen communication within families, improve pediatricians’ knowledge of the issue, and increase the effectiveness of counseling services in schools. Additionally, we suggest that supporting adolescents living in rural areas and expanding access to psychological help mechanisms could play an important role in reducing suicide rates.